Trends in education–occupation mismatch among recent immigrants with a bachelor’s degree or higher, 2001 to 2021 - Christoph Schimmele; Feng Hou (Economic and Social Reports)
Selecting immigrants with high levels of education increases their chances of economic success. Immigrants with a bachelor’s degree or higher are more adaptable to changes in the labour market and have steeper growth in employment earnings than those with a trades or high school education. However, many immigrants with a bachelor’s degree or higher have occupations that underutilize their skills, which can reduce their employment income, productivity and well-being. This article updates previously documented trends in education–occupation mismatch with census data from 2001 to 2021.